Trends and birth outcomes in adolescent refugees and migrants on the Thailand-Myanmar border, 1986-2016: an observational study - Parker, A; Parker, D; Zan, B; Min, A; Gilder, M; Ringringulu, M; Win, E; Wiladphaingern, J; Charunwatthana, P; Nosten, F; Lee, S; McGready, R (Wellcome Trust, 2018)
Background Currently there are more adolescents (10-19 years old) and young adults (20-24 years old) than ever. Reproductive health among this age group is often overlooked, although it can have a profound impact on the future. This is especially the case in conflict zones and refugee settings, where there is a heightened need for reproductive health care, and where both the resources and possibility for data collation are usually limited. Methods Here we report on pregnancies, birth outcomes and risk factors for repeat pregnancies among adolescent and young adult refugees and migrants from antenatal clinics on the Thailand-Myanmar border across a 30 year time span. Results Pregnancy and fertility rates were persistently high. Compared with 20-24-year-olds, 15-19-year-olds who reported being unable to read had 2.35 (CI: 1.97 – 2.81) times the odds for repeat pregnancy (gravidity >2). In primigravidae, the proportion of small for gestational age (SGA) and preterm births (PTB), and neonatal deaths (NND) decreased with increasing maternal age (all p <0.001). After adjustment, this association retained significance for PTB (cut-off point, ≤18 years) but not for SGA and NND. Conclusions There is considerable room for improvement in adolescent pregnancy rates in these border populations, and educational opportunities may play a key role in effective interventions.